Characterisation and functional comparison of single-CRD and multidomain containing galectins CgGal-2 and CgGal-3 from oyster Crassostrea gigas. Issue 78 (July 2018) - Huang, Mengmeng; Zhou, Tao; Wu, Yuehong; Fei, Hui; Wang, Gaoyang; Li, Zhi; Lei, Yutong; Liu, Qian; Sun, Cong; Lv, Zhengbing; Xu, Xue-Wei
Abstract: Galectins are β-galactoside binding lectins that play crucial roles in innate immunity in vertebrates and invertebrates through their conserved carbohydrate-recognition domains (CRDs). In the present study, single- and four-CRD-containing galectins were identified in oyster Crassostrea gigas (designated CgGal-2 and CgGal-3). The open reading frames (ORFs) of CgGal-2 and CgGal-3 encode polypeptides of 200 and 555 amino acids, respectively. All CRDs of CgGal-3 include two consensus motifs essential for ligand-binding, and a novel motif is present in CgGal-2. Pathogen-associated molecular pattern (PAMP) profiles were determined for recombinant rCgGal-2 and rCgGal-3, and rCgGal-2 displayed low binding affinity for PAMPs, while rCgGal-3 bound various PAMPs including glucan, lipopolysaccharide (LPS), and peptidoglycan (PGN) with relatively high affinity. Furthermore, rCgGal-2 and rCgGal-3 exhibited different microbe binding profiles; rCgGal-2 bound to Gram-negative bacteria ( Escherichia coli and Vibrio vulnificus ) and fungi ( Saccharomyces cerevisiae and Pichia pastoris ), while rCgGal-3 bound to these microbes but also to Gram-positive bacteria ( Micrococcus luteus ). In addition, rCgGal-3 possessed microbial agglutinating activity and coagulation activity against fungi and erythrocytes, respectively, but rCgGal-2 lacked any agglutinating activity. Carbohydrate binding specificity analysis showed that rCgGal-3 specifically bound D-galactose. Furthermore, rCgGal-2 and rCgGal-3 functioned as opsonin participating in the clearance against invaders in C. gigas . Thus, CgGal-2 with one CRD and CgGal-3 with four CRDs are new members of the galectin family involved in immune responses against bacterial infection. Differences in the organisation and amino acid sequences of CRDs may affect their specificity and affinity for nonself substances. Highlights: CgGal-2, -3 varied in CRD organisation and key binding motifs functioned as PRR with different nonself-recognition ability. CgGal-3 with four CRDs had broader nonself-recognition spectrum than CgGal-2 with single-CRD. CgGal-3 possessed stronger agglutination activity than CgGal-2, which could be inhibited by D-lactose. CgGal-2 and CgGal-3 could enhance encapsulation of hemocytes against nonself particles.